Incidence rates of in-hospital carpal tunnel syndrome in the general population and possible associations with marital status - Melani Carla; Fateh-Moghadam Pirous; dell'Omo Marco; de Giacomi Giovanna; Bena Antonella; Cooke Robin MT; Curti Stefania; Baldasseroni Alberto; Mattioli Stefano; Biocca Marco; Buiatti Eva; Campo Giuseppe; et al. (BMC Public Health, 2008)
Abstract Background Carpal tunnel syndrome (CTS) is a socially relevant condition associated with biomechanical risk factors. We evaluated age-sex-specific incidence rates of in-hospital cases of CTS in central/northern Italy and explored relations with marital status. Methods Seven regions were considered (overall population, 14.9 million) over 3–6-year periods between 1997 and 2002 (when out-of-hospital CTS surgery was extremely rare). Incidence rates of in-hospital cases of CTS were estimated based on 1) codified demographic, diagnostic and intervention data in obligatory discharge records from all Italian public/private hospitals, archived (according to residence) on regional databases; 2) demographic general population data for each region. We compared (using the χscore test) age-sex-specific rates between married, unmarried, divorced and widowed subsets of the general population. We calculated standardized incidence ratios (SIRs) for married/unmarried men and women. Results Age-standardized incidence rates (per 100,000 person-years) of in-hospital cases of CTS were 166 in women and 44 in men (106 overall). Married subjects of both sexes showed higher age-specific rates with respect to unmarried men/women. SIRs were calculated comparing married vs unmarried rates of both sexes: 1.59 (95% confidence interval [95% CI], 1.57–1.60) in women, and 1.42 (95% CI, 1.40–1.45) in men. As compared with married women/men, widows/widowers both showed 2–3-fold higher incidence peaks during the fourth decade of life (beyond 50 years of age, widowed subjects showed similar trends to unmarried counterparts). Conclusion This large population-based study illustrates distinct age-related trends in men and women, and also raises the question whether marital status could be associated with CTS in the general population.